Using Intervention Mapping to Develop a Provider Intervention to Increase HPV Vaccination in a Federally Qualified Health Center - Jessica D. Austin; Serena A. Rodriguez; Lara S. Savas; Tina Megdal; Lois Ramondetta; Maria E. Fernandez (Frontiers Media S.A., 2020)
Introduction: A healthcare provider's ability to give a strong recommendation for the HPV vaccine is of utmost importance in increasing HPV vaccination. To reduce the burden of HPV-related cancers, there is a critical need to develop and implement theory-based interventions aimed at strengthening healthcare providers' communication about the HPV vaccine.Methods: We used Intervention Mapping (IM) steps 1-5 to develop and implement a provider-level intervention that aligns with the priorities and needs of a large, urban Federally Qualified Health Center (FQHC).Results: In step 1, a diverse planning group identified barriers to HPV vaccination in clinical settings and generated process maps and a logic model of the problem. Step 2 outlined outcomes and provider performance objectives of the intervention and identified knowledge, skills, self-efficacy, outcome expectations, and normative beliefs as modifiable targets that need to change for providers to deliver strong recommendations for the HPV vaccine to parents and patients. In step 3, the planning group mapped the methods of persuasive communication, information, and modeling and skills training to behavioral targets and outlined the program practical applications (strategies) components, scope, and sequence. In steps 4 and 5, the planning group produced the intervention and planned for program implementation. The iterative and participatory process of IM resulted in modifications to the initial intervention that aligned with the needs of the FQHC.Discussion: IM provided a systematic, participatory, and iterative approach for developing a theory-based provider-level intervention aimed at strengthening healthcare providers' ability to provide a strong recommendation for the HPV vaccine to eligible patients and parents served by a large FQHC. IM assisted with the identification of behavioral targets and methods that move beyond HPV knowledge and reminders to create behavior change. IM can help researchers and planners describe the processes and rational behind developing interventions and may help to facilitate implementation in real-world clinical settings by tailoring intervention components to the needs of the population.